Uncovering the potential of mining stocks: Analysis of price prediction and fundamental performance using double exponential smoothing and discounted cash flow - Kamila, Isti; Mushliha; Indrawan; Azka, Muhammad; Sembiring, Brema (Desimal: Jurnal Matematika, 2025)
The purpose of this research was to forecast the stock prices of the mining sector using the Double Exponential Smoothing method and to determine the intrinsic value of stocks using the Discounted Cash Flow method as a recommendation for investment decisions in stocks. The data used was secondary data consisting of closing prices and financial reports from 2022 to 2024 for 10 mining stocks listed on the Main Board of the Energy sector on the IDX website. Based on the results of determining the intrinsic value of the stocks using the DCF method, seven mining stock issuers were categorized as undervalued, namely ABMM, BUMI, BYAN, DEWA, GEMS, HRUM, and INDY, while three other stock issuers were categorized as overvalued, namely ADRO, DSSA, and ITMG. Based on the forecasting results using the Double Exponential Smoothing method, from the seven issuers in the undervalued category, there were two issuers, BYAN and DEWA, that have the potential to experience a price increase. The results of the stock price forecasting evaluation using MAPE show that it was categorized as very accurate with a MAPE value range of 0.6% to 3.5%.